Diplomacy with memory: how the past is employed for future foreign policy - Bachleitner, K (Oxford University Press, 2018)
This article suggests that there exists an alternative form of international political behavior between countries who share a common traumatic past: diplomacy with memory. Diplomacy with memory manifests itself as an official, diplomatic team performance that aims at conveying a certain historic image for the purpose of achieving rational aims on the international stage. In a first step, a theoretical and empirical framework is developed that highlights diplomacy with memory as a strategic diplomatic action that does not conform with mainstream IR models of state behavior. In a second step, the new theoretical model is tested on two selected postconflict scenarios: The bilateral negotiations between West Germany and Israel, and between Austria and Israel about eventual reparation payments to the Jewish state in the early 1950s. Extracting the core elements of the diplomacy with memory from these historical examples, this paper suggests amending the toolkit of traditional diplomatic strategies with memory in order to better explain state behavior in other postconflict situations as they emerge.